The Influence of Gadget Dependency on the Academic Procrastination Levels of Grade 12 STEM Students - Garcia, Maria Isabel; Caraig, Daisy Joy; Carator, Kezia; Oyco, Ma. Theresa; Tababa, Gil Adrienne; Linaugo, Joji; De Oca, Phillip Raymund (Future Science / FSH-PH Publications, 2022)
Excessive phone use has already impacted academic achievement and perceived sociability of students, but the intensity of screen time has worsened with the transition to online learning. Consequently, students tend to delay their tasks as they are easily distracted. This research examines the influence of gadget dependency on the academic procrastination levels of students. It employs a descriptive correlational research design and gathered data from Grade 12 STEM students. Overall, the degree of gadget dependency among students is high, whereas academic procrastination level is moderate, and these two measures have a significant relationship. Analysis shows that students from ROC are significantly higher in both areas. However, sex and screen time do not impact the extent of gadget dependency and academic procrastination. Saliently, learning modality induces gadget dependency and academic procrastination levels. In conclusion, gadget dependency directly affects academic procrastination levels. Findings also suggest further research on other related effects of online and distance learning.